1997
DOI: 10.4315/0362-028x-60.10.1174
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Strains of Escherichia coli Isolated from Milk and Feces of Cows on Dairy Farms in Trinidad

Abstract: The prevalence, counts, and characteristics of Escherichia coli isolated from bulk milk, composite milk, and feces of dairy cows in eight milking centers were determined. The microbial quality of water used during milking was also investigated. Of a total of 175 bulk milk samples studied, 83 (47.4%) contained E. coli compared to only 14 (4.9%) of 287 composite milk samples and the difference was statistically significant (P ≤ 0.001; χ2). The ranges in mean counts of E. coli per milliliter of bulk milk and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
2
13
2
1
Order By: Relevance
“…Adesiyun et al. (1997b) reported a prevalence of 18.5% for strains of VTEC in bulk milk compared with 3.6% in the present study.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Adesiyun et al. (1997b) reported a prevalence of 18.5% for strains of VTEC in bulk milk compared with 3.6% in the present study.…”
Section: Discussioncontrasting
confidence: 64%
“…The use of vero cell cytotoxicity assay determined 10.3% of 595 isolates to be positive for VT production. Amongst the verocytotoxigenic strains, 16.7% of isolates originated from cows’ faeces, a frequency slightly higher than the 14% reported for livestock (cattle, sheep, goats and sheep) in Trinidad by Adesiyun and Kaminjolo (1994), but considerably lower than the 36.6% frequency found in milk and faeces of dairy cows in the country (Adesiyun et al., 1997b). This variation in the frequency of VTEC strains could be time‐related, as the three studies were conducted at different times and they were cross‐sectional studies.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…1994 ; Ansay & Kaspar 1997). However, Adesiyun et al . (1997 ) found that 17 (18·5%) of 94 strains of E. coli isolated from bulk milk and 68 (35·6%) of 204 strains of E. coli isolated from faeces of dairy cows were VTEC strains.…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial resistance of S. aureus and E. coli recovered from raw milk and milk products have been documented by others (Adesiyun, Webb, Romain, & Kaminjolo, 1997;Makovec & Ruegg, 2003;Pitkala, Haveri, Pyorala, & Myllys, 2004;Umoh, Adesiyun, & Gomwalk, 1990b) and it has also been reported that misuse or abuse of antimicrobial agents could result in resistant strains of bacteria in veterinary medicine (Washington, 1979).…”
Section: Introductionmentioning
confidence: 98%